New International Calibration Standard (ICS-I3) for HPLC Analysis of Iso-α-acids: Submitted on behalf of the International Subcommittee for Isomerized Hop α-Acids Standards - Biendl, Martin (BrewingScience, 2009)
The International Subcommittee for Isomerized Hop α-Acids Standards (ISIHAS), announces the release of a new calibration standard, ICS-I3, for the HPLC analysis of iso-α-acids. This standard replaces ICS-I2, which is now withdrawn.